2016
DOI: 10.5014/ajot.2016.017871
|View full text |Cite
|
Sign up to set email alerts
|

Extended Occupational Therapy Reintegration Strategies for a Woman With Guillain-Barré Syndrome: Case Report

Abstract: This case report describes a unique long-term functional recovery process to promote successful community reintegration for a woman with Guillain-Barré syndrome (GBS), a rare autoimmune disease. Her main symptoms were very limited mobility and depressive symptoms due to the unknown cause of and cure for the illness. Holistic occupational strategies helped the client stabilize her emotional state, create a safe home environment, improve a communication method, increase physical activity, and promote social part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…With regard to the treatment of GBS, it is important to improve the physical function of patients, so that patients are able to regain their independent daily life as before the onset of GBS. To date, treatment for GBS has mainly focused on occupational therapy after symptom relief 12 ) . Occupational therapy can help patients with GBS maintain a certain level of daily life; however, there may be some limitations in walking ability and performance of the activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the treatment of GBS, it is important to improve the physical function of patients, so that patients are able to regain their independent daily life as before the onset of GBS. To date, treatment for GBS has mainly focused on occupational therapy after symptom relief 12 ) . Occupational therapy can help patients with GBS maintain a certain level of daily life; however, there may be some limitations in walking ability and performance of the activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Further questions asked respondents to identify specific assessments and interventions applied within their facility. These were informed by tools and interventions described in the literature (for example, Arsenault et al, 2016; Dahi, 2019; Ko et al, 2017; Sawant & Ferzandi, 2015; Tomita et al, 2016). There were a range of response options such as check boxes, 5‐point Likert scales, yes/no questions and those with open‐ended responses which allowed feedback on alternative interventions.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research by physiotherapy authors has identified the efficacy of active ROM (AROM), PROM, splinting, functional mobility, strengthening exercises (Arsenault et al, 2016), isometric and resistance exercises, and neuromuscular electrical stimulation (Nehal & Manisha, 2015; Prada et al, 2020). In addition, occupational therapy research has reported on fatigue management (Sawant & Ferzandi, 2015) and interventions to improve functioning in activities of daily living through provision of adaptations, equipment prescription, and guiding functional use of returning movement in activities of daily living (Dahi, 2019; Ko et al, 2017; Tomita et al, 2016). While the efficacy of common interventions for the upper limb post‐GBS is established, little is known about the contemporary practice on the part of occupational therapists and physiotherapists, including how they integrate goal‐setting tools, assessment tools, and interventions for people with GBS during their hospitalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation